2022
DOI: 10.32604/cmc.2022.020112
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Polio Delayed Epidemic Model via Computer Simulations

Abstract: Through the study, the nonlinear delayed modelling has vital significance in the different field of allied sciences like computational biology, computational chemistry, computational physics, computational economics and many more. Polio is a contagious viral illness that in its most severe form causes nerve injury leading to paralysis, difficulty breathing and sometimes death. In recent years, developing regions like Asia, Africa and sub-continents facing a dreadful situation of poliovirus. That is the reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our review identified nine other studies that presented DEB models of poliovirus transmission for theoretical populations using different numerical simulation methods [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified nine other studies that presented DEB models of poliovirus transmission for theoretical populations using different numerical simulation methods [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bottom portion of Table 2 shows the geographic scope covered by 45 studies that included poliovirus transmission modeling [ 7 , 9 , 10 , 11 , 12 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 67 , 79 , 80 , 81 , 87 , 88 , 89 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Not surprisingly, two groups published studies on Pakistan, Afghanistan and Nigeria, which continue to represent critical geographies for polio eradication.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical techniques with spatio temporal analysis of models are discussed [24,25]. In [26][27][28][29][30][31][32][33][34][35][36], researchers have recently focused on computer simulations of the epidemic model with various delay tactics. The following work studied the related models [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Jesus [17] described the modern history from epidemics to the eradication of poliomyelitis. The deterministic models are investigated using delay techniques as discussed in [18,19]. Hussain et al [20] investigated the dynamics of pine wilt disease using the concept of sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%